2014
DOI: 10.1093/jjco/hyu082
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index and Risk of Gastric Cancer: A Meta-analysis

Abstract: The results indicated that obesity was associated with the risk of gastric cancer, especially for males and among non-Asians. Both overweight and obesity were associated with the risk of gastric cardia cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
69
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(79 citation statements)
references
References 39 publications
(24 reference statements)
8
69
0
2
Order By: Relevance
“…, Lin et al . ), O&O are also associated with various gastrointestinal signs and symptoms (upper abdominal pain, gastro‐oesophageal reflux, diarrhoea, vomiting and retching) in humans. However, among all the gastrointestinal signs examined in the current study, only diarrhoea showed significantly increased odds with BCS.…”
Section: Discussionmentioning
confidence: 99%
“…, Lin et al . ), O&O are also associated with various gastrointestinal signs and symptoms (upper abdominal pain, gastro‐oesophageal reflux, diarrhoea, vomiting and retching) in humans. However, among all the gastrointestinal signs examined in the current study, only diarrhoea showed significantly increased odds with BCS.…”
Section: Discussionmentioning
confidence: 99%
“…Several prospective and retrospective studies have provided support for the hypothesis that higher BMIs in patients are positively associated with a higher incidence of cardiac GC. [17,36,3944] In contrast, no significant link was found between obesity and an increased risk for noncardiac GC. The mechanisms that underlie obesity-induced GC are under investigation.…”
Section: Discussionmentioning
confidence: 96%
“…Chronic inflammation promotes gastric cancer) [9] i) Epstein-Bar virus (EBV) [4] -prefer non-antral location in stomach. EBV gene incorporates into human genes and cause gastric cancer.…”
Section: Risk Factor Of Stomach Cancer A) H Pylori Infection [4] (Clmentioning
confidence: 99%